Theoretical and Methodological Foundations for the Development of Comparative Pedagogy - Chinibayeva, Gulnar (2020)
The article deals with the issues of determining the theoretical foundations of comparative pedagogical research of education systems in Kazakhstan and foreign countries, analyzes the Kazakhstanis and foreign theories. Studies in the field of comparative pedagogy aimed at studying the status, patterns and development trends of pedagogical theory and practice of upbringing and education in different countries of the world and in different historical eras, determining forms, ways and boundaries of transferring the international experience in pedagogy and school practices, predicting future models of education. Currently, the reform of secondary education in Kazakhstan implements more of individualization idea and democratization of education, as well as distinctive feature of Kazakhstan's schools is legally approved right of transition of students from one school to another depending on their abilities.